X-ray radiography investigation of structural conditions of Fe-15Cr-35Ni11W steel irradiated by ion-plasma fluxes - Malynkina, V.G.; Platonova b, E.V. (Elsevier, 2017)
It was found that structural-phase transformations induced by radiation in the highly doped heat resistant Fe-15Cr-35Ni-11W alloy under the effects of treatment with ion-plasma beams differ from the transformations in steels of types 0×18H10T and 0×16N15M3B widely used in nuclear power engineering. Presence of these differences was established by performing X-ray radiography analysis, which demonstrated that additional reflections on the X-ray patterns of irradiated samples of Fe-15Cr-35Ni-11W alloy appear from the side of large angles relative to the reflections for the initial solid solution. Detailed X-ray diffraction studies carried out by the authors showed that additional peaks appeared from the side of smaller angles in the X-ray diffraction patterns of iron-chromium alloys of type 0×18 (10–30) H additionally doped with Ti, Mo, Nb, Al to the amount of 1–3% and irradiated with ion-plasma beams. In both cases the phase thus formed is of isomorphic matrix type and is thermally metastable and, in contrast to 0×18H10T steel, Fe-15Cr-35Ni-11W alloy undergoes softening. The analysis of published data on the possible causes inflicting similar structural-phase transformations in materials subjected to intensive ion-plasma treatment was performed. Concentrations of crystalline lattice stacking faults in Fe-15Cr-35Ni-11W alloy and in 0×18H10T steel in the deformed state were determined by X-ray diffraction analysis. It was found that concentration of structural stacking faults in this state is 4 times higher for 0×18H10T steel, which indicates the lower stacking fault energy in this steel. Conclusion was made that the observed effects are associated with the mechanism of radiation-induced plastic deformation. Structural-phase changes in Fe-15Cr-35Ni-11W alloy are associated with deformation by twinning, in contrast to 0×18H10T steel, where the observed transformations are due to slip deformation. Copyright © 2017, National Research Nuclear University MEPhI (Moscow Engineering Physics Institute). Production and hosting by Elsevier B.V. This is an open access article under the CC BY-NC-ND license. (
full text
Keywords: Ion-plasma treatment; Austenitic stainless steel; X-ray diffraction-pattern; Stacking faults; Slip deformation; Twinning deformation